INDIVIDUAL LEARNING TRAJECTOR IN INCREASE OF EDUCATIONAL EFFICIENCY - Khujayarova Nafisa Sultanmurodovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article describes the pedagogical process of introducing new things into the goals, content, methods and forms of teaching and upbringing, the direction of personal education reflects the process of change in the development and learning of the child, and the organization of joint activities of the teacher and student.